Neutrophil-Lymphocyte Ratio (NLR) Reflects Myocardial Inhomogeneities in Hemodialyzed Patients - Kamila Bołtuć; Arkadiusz Bociek; Robert Dziugieł; Martyna Bociek; Tomasz Zapolski; Wojciech Dąbrowski; Andrzej Jaroszyński (Hindawi Limited, 2020)
Introduction. Cardiovascular diseases (CVDs) are a leading cause of death in chronically hemodialyzed (HD) patients. In this group, inflammation exerts significant impact on the prevalence of CVD morbidity and mortality. Spatial QRS-T angle is an independent and strong predictor of CV events, including sudden cardiac death (SCD), both in general population and HD patients. Pathogenesis of widened QRS-T angle is complicated and is not well established. Objectives. The study is aimed at evaluating whether inflammation process can contribute to the wide QRS-T angle. Patients and Methods. The retrospective study was performed on 183 HD patients. The control group consisted of 38 patients. Demographic, biochemical, vectorcardiographic, and echocardiographic data were evaluated in all patients. Inflammation process was expressed as neutrophil-lymphocyte ratio (NLR), as well as C-reactive protein (CRP). Results. Both NLR (3.40 vs. 1.95 (p<0.0001)) and spatial QRS-T angle (50.76 vs. 93.56 (p<0.001)) were higher in the examined group, compared to the control group. Similarly, CRP was higher in the examined group than in the control group (8.35 vs. 4.06 (p<0.001), respectively). The QRS-T angle correlated with NLR, CRP, some structural echocardiographic parameters, parathormone (PTH), and calcium (Ca) concentrations. Multiple regression analysis showed that NLR is an independent QRS-T angle predictor (r=0.498, p=0.0027). The ROC curve analysis indicated the cut-off point of NLR equaled 4.59, where the sensitivity and specificity were the highest for predicting myocardial inhomogeneities expressed as widened QRS-T angle. Conclusion. The NLR, as an inflammation marker, may indicate myocardial inhomogeneities in HD patients.